Cancer's Lasting Financial Burden: Evidence From a Longitudinal Assessment. (24th March 2022) - Shih, Ya-Chen Tina; Owsley, Kelsey M; Nicholas, Lauren Hersch; Yabroff, K Robin; Bradley, Cathy J
Abstract: Background: The purpose of this study was to conduct a longitudinal analysis of out-of-pocket expenditure (OOPE) trajectories for the assessment of cancer's lasting financial impact. Methods: We identified newly diagnosed cancer patients and constructed matched control group of noncancer participants from the 2002-2018 Health and Retirement Study. Outcomes included monthly OOPE for prescription drugs (RX-OOPE_MONTHLY) and OOPE for medical services other than drugs in the past 2 years (non–RX-OOPE_2YR), consumer debt, and new individual retirement account (IRA) withdrawals. Generalized linear models were used to compare OOPEs between cancer and matched control groups. Logistic regressions were used to compare household-level consumer debt or early IRA withdrawal. Subgroup analysis stratified patients by age, health status, and household income, with the low-income group stratified by Medicaid coverage. All statistical tests were 2-sided. Results: The study cohort included 2022 cancer patients and 10 110 participants in the matched noncancer control group. Mean non–RX-OOPE_2YR of cancer patients was similar to that of participants in the matched control group before diagnosis but statistically significantly higher at diagnosis (1157, P < .001), 2 (511, P < .001) years, 4 (360, P = .006) years, and 6 (430, P = .01) years after diagnosis. A similar pattern was observed in RX-OOPE_MONTHLY. A statistically significantly higher proportion of cancer patients incurred consumer debt at diagnosis (34.5% vs 29.9%; P < .001) and 2 years after (32.5% vs 28.2%; P = .002). There was no statistically significant difference in new IRA withdrawals. Patients experienced lasting financial consequences following cancer diagnosis that were most pronounced among patients aged 65 years and older, in good-to-excellent health at baseline, and with low income, but without Medicaid coverage. Conclusions: Policies to reduce costs and expand insurance coverage options while reducing cost-sharing are needed.